Dampak Pembelajaran Online secara Psikologis pada Siswa SMA - Harits Krishna Rifandi; Herri Christian Palit; Debora Anne Yang Aysia (Jurnal Titra, 2021)
This research was conducted to determine the psychological impact of online learning of high school students. Online learning is being carried out by the government to minimize the spread out of COVID-19 virus. This research uses questionnaires about academic burnout which are distributed by using google form media. Statistic descriptive and crosstabulation are used to analyze and to determine the relationship between respondent profile and academic burnout statement that may affect the psychological burden of high school students. The result showed that all of the high school students experienced moderate level of academic burnout, high school students who experienced disruption during online learning had higher academic burnout, high school student who were more interested in offline learning had higher academic burnout, the higher grade level and the higher usage of video conferencing, then the greater academic burnout experienced by high school students.